KONTRIBUSI MINAT BACA TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS XI SMA NEGERI I KUOK KABUPATEN KAMPAR PROVINSI RIAU - Dwi Viora (JURNAL PENDIDIKAN ROKANIA, 2017)
This research was aims to explain the extent to which the reading interest contributed toward the students’ ability in reading comprehension in class XI of SMA Negeri I Kuok Kabupaten Kampar Provinsi Riau; This was a correlational research whose population was students in class XI of SMA Negeri 1 Kuok Kabupaten Kampar Provinsi Riau registered in academic year 2013/2014. The sample was taken by using total sampling technique, there 53 students was chosen as thesample. The instruments of this research were questionnaires and test which had been tested their validity and reliability. The data gotten then was analyzed by using Pearson Product Moment (PPM) correlation test, multiple correlation test, ttest, F-test, and determinant coefficient formulation to see the extent to which independent variables contributed toward the dependent variable. The result of the research indicated that the students’ reading interests contributed significantly (33,9) toward the students’ ability in reading comprehension because t arithmetic > t table or 5,110 > 1,684. These results indicated that reading interest either contributed significantly toward the students’ ability in reading comprehension in class XI of SMA Negeri 1 Kuok Kabupaten Kampar Provinsi Riau.